2016
DOI: 10.1088/0029-5515/56/10/106021
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the beta-induced Alfvén eigenmode by a plasma flow around the magnetic island

Abstract: It is well known that the rotation of a magnetic island in the reference frame of plasma guiding centers generates parallel electron current outside the island, which is induced by the geodesic curvature of a magnetic field (Smolyakov et al 2007 Phys. Rev. Lett. 99 055002). It is shown in the present work that the surface part of this current located at the island separatrix can drive a pair of counter-propagating, tearing-parity, beta-induced Alfvén eigenmodes, which have the same helicity as that of the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…The fine splittings around each pair of BAEs (presumably for the same |m| and |n|) as shown in figure 7(a) may be attributed to the fine structure of the BAE gaps for the same |m| and |n|. In [51] it has been shown that the pure MHD toroidal Alfvénic (TA) continuum spectra can be described by the differ ential equation (26) with respect to θ for circular flux surfaces, which is a Mathieu equation whose cosine 'potential' reflects the periodic change of the magnetic field strength on each flux surface in toroidal geometry. It is well-known that this equation admits infinite pair of distinct eigen-frequencies and infinite sets of TA gaps delineated by them.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The fine splittings around each pair of BAEs (presumably for the same |m| and |n|) as shown in figure 7(a) may be attributed to the fine structure of the BAE gaps for the same |m| and |n|. In [51] it has been shown that the pure MHD toroidal Alfvénic (TA) continuum spectra can be described by the differ ential equation (26) with respect to θ for circular flux surfaces, which is a Mathieu equation whose cosine 'potential' reflects the periodic change of the magnetic field strength on each flux surface in toroidal geometry. It is well-known that this equation admits infinite pair of distinct eigen-frequencies and infinite sets of TA gaps delineated by them.…”
mentioning
confidence: 98%
“…Furthermore, the novel island-induced Alfvén eigenmodes were identified on a reversed field pinch [20], and the multi-pairs of BAEs have also been observed on LHD [21] during the excitation of strong interchange modes. Several theoretical models have been developed aiming at explaining those phenomena [14,[22][23][24][25][26].…”
mentioning
confidence: 99%
See 3 more Smart Citations